A DESCRIPTIVE STUDY ON TEACHING READING TO THE FIRST YEAR STUDENT OF SMK MUHAMMADIYAH 1 SUKOHARJO - ISTIKOMAH , SITI (2011)
The research paper aims at describing the teaching learning process of teaching reading to the first year student of SMK Muhammadiyah 1 Sukoharjo, to know the classifying the problems faced by the teacher in teaching reading using her method, and to know the describing the strategies implemented by the teacher to overcome the problems. This research is a descriptive qualitative research. The researcher collects the data by observing the classroom activities teaching learning process and conducting interview with the teacher and the students. The data include students’ work, syllabus, and the description of teaching learning process. The methods of collecting the data are the observation, interview, and documents. From the research finding and discussion, the researcher draws the following conclusion. The research finding shows that the first, describing the teaching learning process of teaching reading to the first year student in SMK Muhammadiyah 1 Sukoharjo were done for three times. In the first meeting, the teacher used four cycles in teaching-learning process in clearly and maximally. The second meeting, the teacher improved the material by giving various methods in order to the students were interested with the lesson. Then the third meeting, the teacher less in engaged the students in modeling of text and joint construction of text. The second, the problems faced by the teacher in teaching reading using her method are; (a) the teacher gets difficulties in controlling the students in the class, (b) the students have less motivation in learning English, (c) the teacher has a limited time, (d) the students have limited of vocabulary, and (e) the students have not clear pronunciation. The third, the strategies implemented by the teacher to overcome the problems are; (a) the teacher can control the class by walking around the class when teaching learning process run (b) the teacher needs more time to teach English, (c) the teacher needs more time to communicate with the students, (d) the teacher needs clearing and developing the students’ pronunciation, (e) the teacher needs increasing and memorizing the students’ vocabulary.